Bond market access and investment - Harford, Jarrad; Uysal, Vahap B. (Journal of Financial Economics, 2014)
Prior research has shown that differential access to debt markets significantly affects capital structure. In this paper, we examine the effect of access to debt markets on investment decisions by using debt ratings to indicate bond market access. We find that rated firms are more likely to undertake acquisitions than nonrated firms. This finding remains even after accounting for firm characteristics, for the probability of being rated, and in matched sample analysis as well as in subsamples based on leverage, firm size, age and information opacity. Rated firms also pay higher premiums for their targets and receive less favorable market reaction to their acquisition announcements relative to non-rated firms. However, the average announcement returns to rated acquirers are non-negative. Collectively, these findings suggest that the lack of debt market access has a real effect on the ability to make investments as well as on the quality of these investments by creating underinvestment, instead of simply constraining overinvestment.